'Talk of the town': Explaining pathways to participation in violent display. (September 2017) - Fujii, Lee Ann
How do people come to participate in violent display? By 'violent display', I mean a collective effort to stage violence for people to see, notice, or take in. Violent displays occur in diverse contexts and involve a range of actors: state and non-state, men and women, adults and children. The puzzle is why they occur at all given the risks and costs. Socialization helps to resolve this puzzle by showing how actors who have consciously adopted or internalized group norms might take part, despite the risks. Socialization is more limited in explaining how and why actors who are not bound by group norms also manage to put violence on display. To account for these other pathways, I propose a theory of 'casting'. Casting is the process by which actors take on roles and roles take on actors. Roles enable actors to do things they would not normally do. They give the display its form, content, and meaning. Paying attention to this process reveals how violent displays come into being and how the most eager actors as well as unwitting and unwilling participants come to take part in these grisly shows. To explore variation in the casting process, I investigate violent displays that occurred in two different contexts: the Bosnian war and Jim Crow Maryland. Data come from interviews, trial testimonies, and primary sources.